MUTED VOICES: DEVOLUTION OF WOMEN THROUGH HISTORY (Proceedings of the World Conference on Women’s Studies, 2017)
Suppression and characterization is a common concernassociated with the lives of women. They have been subdued and assigned secondary roles for a prolonged period, which has outlined the mind-set of people. Gender roles and traditional beliefs have constrained the thought process of the society, in turn creating a lacuna in the system that has transformed itself into an acknowledged norm. Women are commodified and exploited which is widely accepted and normalized, at the same time, they are labelled and out casted if they step out of their restrained social construct. This status of women has been consistent throughout the evolution of the society. Her freedom is either limited by the society or criticized by it. Although we have women in high political positions and as global leaders, their journey towards success can be defined through struggles. This paperanalyses the influence of historical beliefs in modern day usage, considering women in divergent roles, the idea of a glass ceiling, advent of lesbian culture, roles played after marriage and so on. Various instances are consideredto portray and critique the development from the purdah system to the urbanized progressive woman. The paper also establishes an understanding to the psychological restrains towards the development of women across the globe.
Keywords: normalization; commodification; stigmatization; self-restraint; exploitation